Assessing the impact of disaster-induced displacement from climate-induced water hazards : a case study from Melamchi, Nepal - Dhungel, Yathartha; Pal, Indrajit; Srinivasan, Govindrajalu; Ahmad, Mokbul Morshed; Asian Institute of Technology Scholarships; RIMES Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Disaster-induced displacement is an increasingly rising concern globally and nations that are at high risk of multi-hazard impacts such as Nepal, face immense challenges to reduce disaster-induced displacement trends. Disaster impacts caused by both geophysical and climate-induced water hazards are prominent in Nepal with the latter displacing more people over the long-run. Localized events such as flash floods, mudslides, earthquakes, landslides, glacial lake outburst floods and other hazards displace smaller populations living in varrying terrains, across Nepal. The impact of multiple disasters have also displaced many families on more than three separate occassions. The 2021 Melamchi flood is a localized event affecting 635.19 sq. KM area in Sindhupalchowk district that experienced cascading impact of a complex climate-induced water hazard on 10th June{u2019}2021, that has affected more than 84,000 people, displaced 801 households and mounted an economic loss of USD 532 million in the wake of the cascading impacts. Multiple cascading impacts including GLOF,LDOF and riverbank erosion, driven by intense rainfall rendered the victims homeless, forcing them to still await compensation from the government authorities almost two years after the disaster struck. Disaster risks are deeply rooted in the Nepalese context as during the monsoon season, the population is used to 2badhi-pahiro3, flood and landslide , but were unprepard and unaware of cascading impacts. The field visit conducted on January 2023, shed light on the plight of the victims as 100 displaced households were visited ; 47/100 households visited were still living in make-shift temporary shelters that are prone to further damage by thunderstorms. However, disasters may bring opportunities for economic avenues and provide options for risk-sensisitive, DRR inclusive development practices, and nation-wide disaster monitoring and MHEWS, as suggested by the NDRRMA. DID is caused by such processess that can be measured by science and therefore, can be modelled, estimated and thus, prevented.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Disaster Preparedness, Mitigation and Management, School of Environment, Resources and Development {u2013} School of Engineering and Technology
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Climate change -- Nepal -- Melamchi; Disasters -- Nepal -- Melamchi; Floods -- Risk assessment -- Nepal -- Melamchi